Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijms23063199
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cardiotoxicity Assays Using Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes (hiPSC-CMs)

Abstract: Cardiomyocytes (CMs) differentiated from human induced pluripotent stem cells (hiPSCs) are increasingly used in cardiac safety assessment, disease modeling and regenerative medicine. A vast majority of cardiotoxicity studies in the past have tested acute effects of compounds and drugs; however, these studies lack information on the morphological or physiological responses that may occur after prolonged exposure to a cardiotoxic compound. In this review, we focus on recent advances in chronic cardiotoxicity ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Following the treatment with different cardiotoxic drugs, we observed a dosedependent effect on CM viability and changes in myocardial architecture. Over the past decade, many studies have shown the use of iPSC-CMs to assess the cardiac toxicity of different drugs (Narkar et al 2022;Sharma et al 2017;Thomas et al 2021). However, monitoring live CMs at different drug concentrations gives an additional application of the reporter CMs on drug dose effects and identifies drugs that interfere with the CMs contractile machinery but may not directly impact the CMs electrophysiology and viability.…”
Section: Discussionmentioning
confidence: 99%
“…Following the treatment with different cardiotoxic drugs, we observed a dosedependent effect on CM viability and changes in myocardial architecture. Over the past decade, many studies have shown the use of iPSC-CMs to assess the cardiac toxicity of different drugs (Narkar et al 2022;Sharma et al 2017;Thomas et al 2021). However, monitoring live CMs at different drug concentrations gives an additional application of the reporter CMs on drug dose effects and identifies drugs that interfere with the CMs contractile machinery but may not directly impact the CMs electrophysiology and viability.…”
Section: Discussionmentioning
confidence: 99%
“…How to cite this article: Narkar, A., Feaster, T. K., Casciola, M., & Blinova, K. (2022). Human in vitro neurocardiac coculture (ivNCC) assay development for evaluating cardiac contractility modulation.…”
Section: Funding Informationmentioning
confidence: 99%
“…Primary and secondary antibodies were diluted in 2.5% (wt/vol) bovine serum albumin (BSA)/PBS/0.5% Triton X-100. Specimens were incubated with primary antibodies Cardiac troponin (Catalog # MA5-12960, Invitrogen), Peripherin (Catalog # AB1530, EMD Millipore) at 1:500 overnight, washed three times for 5-10 min, and incubated with fluorescently conjugated secondary antibodies for 2-4 h as described in detail elsewhere (Narkar et al, 2021). All washes were performed with PBS/0.5% Triton X-100.…”
Section: Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Although hiPSC-CMs can be maintained in culture for long periods of time with stable baseline functions (Kopljar et al 2017;Dias et al 2018), the current methods such as patch-clamp, voltage indicators, and MEA technology do not offer at the same time high sensitivity for measuring transmembrane ion currents and low-invasiveness for 3 monitoring cells over long time. Therefore, despite the recent advances in chronic cardiotoxicity assays using hiPSC-CMs (Narkar et al 2022), long-term (chronic) cardiac adverse effects remain a major barrier of drug development. The in vitro detection of chronic cardiotoxicity represents a key turning point to avoid the progression of a drug candidate with "delayed" cardiac adverse effect.…”
Section: Introductionmentioning
confidence: 99%